2007 International Workshop on Physics of Semiconductor Devices 2007
DOI: 10.1109/iwpsd.2007.4472559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post deposition annealing temperature on the properties of ZnO films prepared by RF magnetron sputtering

Abstract: Highly C-axis oriented ZnO films were deposited by RF magnetron sputtering technique on unheated Si substrate with SiO 2 layer deposited using thermal oxidation. We employ thermal annealing techniques with temperature range from 350˚C to 800˚C to investigate quality of annealed ZnO substrates. Post deposition annealing of ZnO films at atmospheric pressure in oxygen at different temperatures were found to improve film structure such as dense structure, smooth surface, and increasing resistivity. The surface mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…This precursor needs to be spun on and subjected to postdeposition annealing. In general, to improve structural and optical properties of the deposited oxide on a substrate, post-deposition annealing is performed at various temperatures and ambients [52][53][54]. The effects of annealing temperature and ambient have been shown by pulsed laser deposited [55] and RF magnetron sputtered tantalum oxide (Ta 2 O 5 ) [56], successive ionic layer adsorption and reaction technique deposited [57] as well as pulsed laser deposited ZnO film [31], and pulsed laser deposited titanium oxide (TiO 2 ) thin film [58], indicating that physical properties of the deposited films were improved.…”
Section: Introductionmentioning
confidence: 99%
“…This precursor needs to be spun on and subjected to postdeposition annealing. In general, to improve structural and optical properties of the deposited oxide on a substrate, post-deposition annealing is performed at various temperatures and ambients [52][53][54]. The effects of annealing temperature and ambient have been shown by pulsed laser deposited [55] and RF magnetron sputtered tantalum oxide (Ta 2 O 5 ) [56], successive ionic layer adsorption and reaction technique deposited [57] as well as pulsed laser deposited ZnO film [31], and pulsed laser deposited titanium oxide (TiO 2 ) thin film [58], indicating that physical properties of the deposited films were improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the challenges facing the applications of this important material is the fabrication of films with adequate quality, having low electrical resistivity and high optical transmittance. It has been found that obtaining good material properties depend on the deposition conditions and post annealing processes [5,6]. Thus, in order to understand this influence better, we investigated the influence of RF power on the film properties, using RF magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%